Nursing consultation to the patient with diabetes mellitus and arterial hypertension – experience report - Silva, Ana Roberta Vilarouca da; Costa, Francisca Bertilia Chaves; Araújo, Thelma Leite de; Galvão, Marli Teresinha Gimeniz; Damasceno, Marta Maria Coelho (Rev Rene, 2007)
The aim of this research was to report the experience of the Nursing process based on Orem’s Self-care Theory. The study was accomplished from November to December 2005 with an aged hypertensive diabetic woman at her house. Departing from a nursing consultation we identified the problems, International Classification for Nursing Practice (ICNP) problems, established the Nursing diagnoses, using the International Classification for Nursing Practice (CIPE) – beta 2 version and were also elaborated prescriptions, plans and evaluations. It was highlighted the applicability, in the practice, of the Nursing process based on Orem and the importance of Nursing diagnoses as a guidance for the care to be given.